FAKTOR YANG BERHUBUNGAN DENGAN FUNGSI KOGNITIF PASIEN GAGAL GINJAL KRONIS DI RUANGAN HEMODIALISA - Widia Lestari; Rahma Annisa; Erni Buston (MNJ (Mahakam Nursing Journal), 2021)
Abstract Background: Treatment of patients with chronic renal failure (CRF) presents challenges to health care providers. Parallel neuropathological changes in the brain have been put in place as a mechanism explaining the link between impaired cognitive function and chronic renal failure. Objective: To identify the relationship between the length of hemodialysis, complications of CVD, anemia and uremia on cognitive function. Methods: This research is a descriptive-analytic study with a cross-sectional study design. The sample in this study were chronic kidney failure patients in the Hemodialysis Room Dr. M. Yunus Bengkulu In 2018, there were 140 people. Cognitive function data were collected directly by filling out a questionnaire with the Moca-INA method, data on length of hemodialysis, urea levels, complications of CVD and haemoglobin levels were obtained from the patient's medical records. Data analysis was carried out quantitatively, namely univariate, bivariate and multivariate. The results: there was a significant relationship between cardiovascular disease and cognitive function, there was a significant relationship between blood urea levels and cognitive function. Blood urea level is the factor most closely related to lung capacity. Suggestion: that the decline in cognitive function occurs in the majority of CKD patients but is not detected by health workers, so it needs good collaboration between nurses, kidney specialists and neurologists.